Evaluation of the effects of different polishing systems on surface roughness and surface discoloration of various restorative materials - Tuba Sarıcı; Burak Dayı (BMC Oral Health)
Abstract Objective This in-vitro study aimed to evaluate the effects of different polishing systems on the surface roughness and discoloration of various composite resins, and to assess the effectiveness of repolishing procedures in reducing discoloration. Materials and methods Four different composite resins (giomer, nanohybrid, nanoceramic, microhybrid) were polished using various systems. Surface roughness was evaluated using mechanical profilometer, Atomic Force Microscopy (AFM). Surface morphology was examined by Scanning Electron Microscopy (SEM). Samples were immersed in a coffee solution for staining, followed by repolishing. Color change (ΔE) values were recorded. Results Surface roughness and discoloration varied based on the composite type and polishing system. The smoothest surface was observed in the nanohybrid composite polished with OptiDisc (Ra: 0.59), while the roughest surface was seen in the nanoceramic composite polished with Lucida (Ra: 1.70). The highest discoloration occurred in the giomer with Enhance PoGo, while Twist Dia produced the most stain-resistant surfaces (p = 0.008). Repolishing with the OptiDisc significantly reduced discoloration, with ΔE values falling within clinically acceptable limits only in this group (p = 0.00671). Conclusions Multi-step polishing systems, those containing aluminum oxide were more effective in achieving smoother surfaces and better color stability. Results varied according to the composite material and the polishing system used. Clinical significance This study emphasizes that different polishing systems may lead to differences that could potentially affect the clinical performance and aesthetic longevity of composite resins.